International Paralympic Committee (IPC) and International Blind Sports Federation (IBSA) joint position stand on the sport-specific classification of athletes with vision impairment - Mann, D. L.; Ravensbergen, H. J. C. (Sports Medicine, 2018)
Classification is a defining characteristic of para-sports whereby eligible athletes are allocated a sport class to compete against others with similar activity limitations. To account for the unique characteristics of each sport, para-sports should develop their own classification system using evidence that demonstrates the impact of impairment on performance in that sport. Although the move towards sport-specific classification has progressed in sports for athletes with physical and intellectual impairments, sports for athletes with vision impairment (VI) continue to use the same three classes irrespective of the sport, with classes delineated by legal definitions of low vision and blindness. The aim of this joint International Paralympic Committee/International Blind Sports Federation (IPC/IBSA) Position Stand is to provide guidance for how evidence-based sport-specific classification should be achieved in VI sports. It does so by outlining three conceptual research models (correlation, simulation, and component analysis) that can be used to establish both the minimum impairment required to compete plus the appropriate number of sport classes and their inclusion criteria. The present evaluation of vision relies on measures of visual acuity and field, but new criteria may require a sport-specific combination of additional measures of visual function (e.g. contrast, motion, and light sensitivity) to better account for the impact of VI on sport performance. Moreover, the test procedures used during athlete evaluation (e.g. whether to evaluate both eyes individually or together) should be chosen to better represent the habitual viewing situation experienced in that sport. The development of sport-specific criteria should enhance the legi